Directives in English language newspaper editorials across cultures. (December 2017) - Masroor, Farzana; Ahmad, Ummul Khair
Highlights: The study explored argumentative stance in English newspaper editorials. The use of directives was analysed with respect to frequency, form and co-text. There were differences in stance of Pakistani, American and Malaysian newspapers. The situational factors were influential in shaping argumentative structures. Abstract: In opinion discourse like newspaper editorials, written arguments exhibit an interesting interplay of linguistic features and strategies to achieve the communicative purpose of persuading the audience which is worth investigating especially in cross cultural settings. The intentions of editorials are fulfilled most explicitly through the strategy of directives, where facts may be provided only to endorse editorial stance. A pragma-dialectical approach to discourse analysis assumes argument structures as speech acts which require careful analysis of text and context. In this vein, this study analysed directives in 90 English editorials, taken from two Asian ( Dawn and New Straits Times ) and one American newspaper ( The New York Times ), by looking at their form, frequency and co-text. The results indicate Dawn 's stance when realizing directives as direct, NYT 's stance was authoritative, whereas NST's stance was less engaging and more cautious.